Teaching of thermology: a proposal of didactic sequence based on the historical-critical pedagogy (Research, Society and Development, 2021)
In this article we present a didactic sequence that was developed for teaching of concepts of Thermology based on theoretical assumptions of historical-critical pedagogy (HCP). This pedagogy understands man as a historical being, built over time, and education as a fundamental process for this humanization. The didactic sequence, which has the theme “Global warming”, was structured based on the five structuring steps of HCP and experienced with students of the second grade of High School, during physics classes. Throughout the activities the students were observed and answered a questionnaire. With the observations and analysis of the responses, an empirical study with a qualitative approach was developed. The analysis of the data after the activities of the didactic sequence confirmed a greater knowledge on the part of the students about the concepts of Thermology discussed in comparison to the initial moment of the sequence. These students' diverse reactions, such as demonstrations of autonomy, spontaneity, and expectation to participate in the sequence's actions, confirmed that the five steps proposed in HCP contributed to their understanding of the social context.